EndoS: An SPSS macro to assess endogeneity - Daryanto, Ahmad (Tutorials in Quantitative Methods for Psychology, 2020)
In this tutorial, I demonstrate how to address endogeneity with instrumental variable regression using my newly developed EndoS macro for SPSS. EndoS implements the generalized instrumental variable estimator in the form of a two-stage least square (TSLS) estimator and is capable of performing three endogeneity diagnostic tests indispensable in empirical IV regression papers: Hausman's specification tests, overidentifying restriction tests and weak instrument tests. I present two illustrative examples using data from published studies.